Evaluating an EFL Textbook: A Good Fit, Adequate Fit, a Poor Fit or Totally Wrong? - Aprilia, Fitria; Neisya (Indonesian Research Journal in Education |IRJE|, 2023)
This research aimed to investigate an evaluation of an EFL textbook for senior high school students entitled â€œFunctional English for Senior High Schoolsâ€ written by Sugeng and Zaimah (2007). The book was published in 2007 by Tiga Serangkai Pustaka Mandiri, Solo. The researchers used a qualitative evaluation checklist, namely â€œEvaluation of the Fitâ€ by Byrd et al. (2001) by evaluating the fitness of textbooks through three aspects: curriculum, students, and teachers. The evaluation results are: (1) considering the curriculum aspect, the book was categorized as a good fit, (2) considering the fitness of the book with the studentsâ€™ needs. It was categorized as a good and adequate fit. However, (3) considering the teachersâ€™ aspect, the book was considered a poor fit because it was not completed with supplementary teaching materials, such as cassettes or CDs and manual supports for teachers. The conclusion showed the textbook was categorized as an adequate fit for the curriculum, students, and teachers, and it needed manual and technological support for a more beneficial function.